Effect of hyperoxia on metabolic responses and recovery in intermittent exercise - Nummela, A.; Hamalainen, I.; Rusko, H. (Scandinavian Journal of Medicine & Science in Sports, 2002)
The aim of the present study was to investigate whether the breathing of hyperoxic gas affects hemoglobin oxygen saturation (SaO2) and blood acidosis during intense intermittent exercise and recovery in sprint runners. The hypothesis was that the breathing of hyperoxic gas prevents SaO2 from decreasing, delays blood acidosis during the exercise and improves the rate of heart rate recovery after the exercise. Nine sprinters ran three sets of 300 m at different velocities on a treadmill in normoxia (NOX) and in two hyperoxic conditions (ERHOX and RHOX; FIO2 0.40) in a randomized order. In ERHOX the inspired air was hyperoxic during the entire exercise and recovery and in RHOX the hyperoxic air was only inhaled during recovery periods. Blood pH and SaO2 were measured from fingertip blood samples taken after each set of runs. The mean heart rate for the final 15 s of the last run in each set (HRwork), the mean heart rate for the final 15 s of the first minute of recovery (HRrec) and the difference of HRwork and HRrec (HRdec) were determined. In NOX, SaO2 decreased from 95.0 +/- 2.0% to 88.7 +/- 2.0% (p < 0.001) but SaO2 did not change in ERHOX (from 95.4 +/- 1.3% to 95.9 +/- 1.8%). A significant correlation was observed between the SaO2 decrease in NOX and the effect of hyperoxia on blood pH in ERHOX (r = 0.63) and on HRdec in both ERHOX (r = 0.74) and RHOX (r = 0.69). We concluded that hemoglobin oxygen de-saturation occurred during intensive intermittent exercise in normoxia but hyperoxic gas during the exercise prevents SaO2 from decreasing. Furthermore, the present results suggested that the beneficial effects of hyperoxia on heart rate recovery and blood acidosis during intensive intermittent exercise were related to hemoglobin de-saturation in normoxia.